PENGARUH KUALITAS PELAYANAN DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA KANTOR DISDUK CAPIL DI KOTA BATAM - Putri Dewanti, Arlisa; Winda Evyanto, S.S., M.MPd., Winda Evyanto, S.S., M.MPd. (SCIENTIA JOURNAL, 2023)
This study means to decide the impact of the variable model of Administration Quality,Worker Execution on Local area Fulfillment. Analysts utilized this kind of unmistakableexamination involving quantitative strategies in which the information acquired wereinformation from polls (surveys). The number of inhabitants in this study is the local areawho oversees reports at DISDUK CAPIL Batam city whose number can't be anticipated,so an example is taken utilizing the Nonprobability Testing technique in which the quantitynot set in stone by the scientist is 100 respondents. The consequences of informationexamination utilizing the assistance of the SPSS application rendition 29 found that thecost variable has a t-count esteem more prominent than t-table or (2.211 > 1.660) or Ha isdismissed and Ho is acknowledged which implies the speculation expresses that the HelpQuality variable has an impact decidedly and somewhat important to local area fulfillmentcan be acknowledged. While the Worker Execution Variable gets a t-count esteem moreprominent than t-table or (1.986 > 1.660) or Ha is dismissed and Ho is acknowledged, andthat implies that the speculation which expresses that the Representative Presentationvariable has a positive and to some extent massive impact on Local area Fulfillment isOK. The consequences of the F test on the Factors of Administration Quality and WorkerExecution get a f-count esteem more noteworthy than the f-table or (3.37 > 3.09), and thatimplies that Ha is dismissed and Ho is acknowledged or the speculation expresses thatHelp Quality Factors and Factors Representative Execution all the while or togetheraltogether affects Local area Fulfillment Factors, OK